Meningkatkan Kemampuan Bekerja dengan Grafik melalui Pembelajaran Kinematika - Nurul Hidayah; Sutopo Sutopo; Hari Wisodo (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2019)
Abstract: This research examines the increase of students’ ability in working with graph. This research is conducted by involving 58 students in class X SMA Negeri 5 Malang as the subjects. Students are given kinematics learning by making models of various representations including graphics. The ability of students are assessed using multiple choice questions in graphic format. The improvement  of students’ ability is observed from the average score  pretest and posttest. The analysis shows that there is a significant increase (p = 0.00) with the results of the N-Gain calculation of 0.25 including the medium category. Students are able to change the understanding of graph after learning even though the WYSIWYG effect is still very influential on the way students interpretation graph.Abstrak: Penelitian ini mengkaji peningkatan kemampuan siswa bekerja dengan grafik. Penelitian dilakukan dengan subjek 58 siswa kelas X SMA N 5 Malang. Siswa diberikan pembelajaran kinematika dengan membuat model berbagai representasi termasuk grafik. Kemampuan siswa diukur menggunakan soal-soal multiple choice dalam format grafik. Peningkatan kemampuan siswa ditinjau dari skor rata-rata pretest  dan posttest. Analisis menunjukkan ada peningkatan signifikan (p=0,000) dengan hasil perhitungan N-Gain sebesar 0,25 termasuk kategori sedang. Siswa mampu mengubah pemahaman tentang grafik setelah pembelajaran meskipun efek WYSIWYG masih sangat berpengaruh pada cara siswa menginterpretasikan grafik.